(untitled) (Research, Society and Development, 2020)
This study aimed to identify the feelings experienced by professionals from the Cleaning and Disinfection Service in Health Services during their work activity. To this end, an exploratory-descriptive study with a qualitative approach was carried out in a Hospital located in the interior of the State of Rio de Janeiro with 29 professionals from the Cleaning and Disinfection Service in Health Services, from July to August 2019 through dialogic interviews with a script of open questions through audio recording, with subsequent analysis and discussion of data. In view of the analysis, it was possible to create thematic axes, and to discuss, the following results were obtained: "... suffering with the feelings of others ..." and "... enjoying working ..." as the most cited feelings by respondents and “concern for the sick” as the most cited impact. In view of the above, it was possible to conclude that training is necessary for this team, which deals many times to better instruct and improve the cleaning work and assist them in the adversities encountered during the service, the support of a multidisciplinary team can help to alleviate possible feelings and interferences in the quality of life of the professionals involved in this type of service.